Get Shorty [videorecording (Blu-Ray)] - Travolta, John, 1954-; Hackman, Gene; Russo, Rene; DeVito, Danny; DeVito, Danny; Travolta, John, 1954-; Shamberg, Michael; Sher, Stacey; Sonnenfeld, Barry (Twentieth Century Fox Home Entertainment, 2012)
Loan shark Chili Palmer is bored with the business. So when he arrives in LA to collect a debt from down-and-out filmmaker Harry Zimm, Chili talks tough, and then pitches Harry a script idea. Immediately, Chili is swept into the Hollywood scene: He schmoozes film star Martin Weir, romances B-movie queen Karen Flores and even gets reservations at the hottest restaurants in town. Bonus features included.